2016
DOI: 10.1177/0884533616661011
|View full text |Cite|
|
Sign up to set email alerts
|

Transition to a Tube Feeding Formula With Real Food Ingredients in Pediatric Patients With Intestinal Failure

Abstract: Due to concerns related primarily to allergic response and malabsorption, enteral nutrition therapy has traditionally relied on the use of elemental formulas in children with intestinal failure (IF). Blended food diets via a gastrostomy tube have been reported to improve feeding tolerance in pediatric populations receiving long-term enteral nutrition therapy. Complex macronutrients have been shown to stimulate intestinal adaptation in animal models. We report on our experience in children with IF who had an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 13 publications
5
75
0
1
Order By: Relevance
“…Although the development of constipation has not been reported previously, this symptom was not formally assessed in other studies . Another study noted decreased stool output in children with intestinal failure and diarrhea when they received blended diets . These authors hypothesized that the complexity of whole foods and the increased amount of long‐chain fatty acids contained in the blended diets (compared with standard formulas) may stimulate gut adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the development of constipation has not been reported previously, this symptom was not formally assessed in other studies . Another study noted decreased stool output in children with intestinal failure and diarrhea when they received blended diets . These authors hypothesized that the complexity of whole foods and the increased amount of long‐chain fatty acids contained in the blended diets (compared with standard formulas) may stimulate gut adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Another study noted decreased stool output in children with intestinal failure and diarrhea when they received blended diets. 10 These authors hypothesized that the complexity of whole foods and the increased amount of long-chain fatty acids contained in the blended diets (compared with standard formulas) may stimulate gut adaptation. Also highlighted was the suggestion that the variety of fiber types found in a blended diet may alter the gut microbiota, disfavoring dysbiosis and benefiting nutrient absorption and therefore decreasing diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that 433 parents of blended‐fed children reported their children had fewer gastrointestinal symptoms with blended feeds than with standard formula and, when these occurred, attributed them to the child's medical condition rather than food‐borne illness associated with feeding . Similarly, improvements in bowel habits associated with receiving blended feeds have been reported . The positive role of microbes in gastrointestinal health needs consideration because these may be contributing to some of the improvements reported by those using or preparing blended feeds.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of the fibre content of commercial enteral feeds highlighted concerns about mineral retention in fibre used in formula and other effects of formula fibre, including bloating, gas and cramps (26) . More recently, researchers suggested that a blended diet may improve stooling patterns by incorporating complex whole food nutrients and varying types and quantities of fibres and fats (27) . A study investigating the properties of commercial formulas found a lack of the necessary bacteria present in a normal diet that help maintain normal gut function and, in addition, antioxidants and bioflavonoids required for long-term prevention of disease were absent (28) .…”
Section: Nutritional Valuementioning
confidence: 99%